2013
DOI: 10.1148/radiology.13121981
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET Uptake as a Predictor of Pain Response in Palliative Radiation Therapy in Patients with Bone Metastasis

Abstract: To evaluate the relationship between fluorine 18 fluorodeoxyglucose (FDG) positron emission tomography (PET) maximum standardized uptake value (SUV max ) and pain response to radiation therapy (RT) in patients with bone metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Several studies have indicated that SUVmax assessed with FDG-PET is a predictive biomarker of initial pain severity in patients with malignancy. [17][18][19][20] Our findings confirm that the FDG-PET SUVmax in metastatic bone lesions is associated with painful bone metastasis in patients with lung cancer, suggesting that biological and/or metabolic parameters determined using FDG-PET could be useful to evaluate the status of metastatic bone lesions in lung cancer patients. In addition, we showed that increased SUVmax was associated with subsequent SREs during the clinical course in patients with lung cancer, which has not been evaluated by previous studies.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Several studies have indicated that SUVmax assessed with FDG-PET is a predictive biomarker of initial pain severity in patients with malignancy. [17][18][19][20] Our findings confirm that the FDG-PET SUVmax in metastatic bone lesions is associated with painful bone metastasis in patients with lung cancer, suggesting that biological and/or metabolic parameters determined using FDG-PET could be useful to evaluate the status of metastatic bone lesions in lung cancer patients. In addition, we showed that increased SUVmax was associated with subsequent SREs during the clinical course in patients with lung cancer, which has not been evaluated by previous studies.…”
Section: Discussionsupporting
confidence: 70%
“…[17][18][19][20] SUVmax assessed with FDG-PET/CT is a predictive biomarker of initial pain severity, 17,18 and decreased SUVmax after palliative radiotherapy for metastatic bone sites is a significant predictor of the response in patients with bone pain. [18][19][20] However, these studies did not focus on patients with lung cancer alone, and limited information is available regarding FDG-PET/CT assessment in metastatic bone lesions in patients with lung cancer. To our knowledge, there have been no previous studies of FDG-PET/CT assessment of bone metastasis in patients with lung cancer, particularly according to histological differences, the presence of bone metastatic pain, and the subsequent development of SREs.…”
Section: Introductionmentioning
confidence: 99%
“…It is also of interest that SUVmax was higher in the irradiated areas, which by default, were the areas where pain was the most severe. This association has not previously been reported in lung cancer or MPM per se, however, it has been demonstrated that increased SUV uptake is associated with increased pain and subsequent response to radiotherapy in bone metastases (9). The present study was not powered to examine whether increased SUVmax predicted increased likelihood of response to radiotherapy, but this would be of interest in future work.…”
Section: Discussionmentioning
confidence: 64%
“…A high 18 F-FDG-uptake is correlated with increased local failure following radiotherapy [34][35][36][37] and it is hypothesized that 18 F-FDG-avid regions coincide with regions of radioresistance, [34][35][36][37] requiring a higher radiation dose. 38,39 In bone metastases, it was recently demonstrated that a high SUV MAX is correlated with initial pain severity and lower pain response to conventional radiotherapy 40 and cryoablation. 41 The median SUV MAX value of bone metastases is around 7-9, 31,40 which is approximately four times higher compared to SUV MAX values in normal bone.…”
Section: Structurementioning
confidence: 99%
“…38,39 In bone metastases, it was recently demonstrated that a high SUV MAX is correlated with initial pain severity and lower pain response to conventional radiotherapy 40 and cryoablation. 41 The median SUV MAX value of bone metastases is around 7-9, 31,40 which is approximately four times higher compared to SUV MAX values in normal bone. 31 Consequently, bone metastases might be ideal candidates to deliver a nonuniform radiation dose distribution, based on the 18 F-FDG-PET information.…”
Section: Structurementioning
confidence: 99%